Generating Local Needs Through Technology: Global Comparisons in Diabetes Quality Management. Issue 3 (1st September 2016) - Rogvi, Sofie á; Juul, Annegrete; Langstrup, Henriette
Abstract : The rhetoric of need is commonplace in discourses of technology and innovation, as well as in global health. Users are said to have a need for innovative technology, and citizens in resource-poor regions to have a need for improved health care. In this article we follow a global health technology—more specifically, a piece of software for monitoring diabetes quality—from Denmark, where it was developed, to Jakarta, Indonesia, where it was introduced in 2012–13. Using ethnographic material, we show how the need for a specific technology is constituted through the very process of moving a technology from one setting to another. Central to this process of a technology traveling, we suggest, is the role played by comparisons invoked by actors and the technology itself. These comparisons become instances of evaluating local practices, thus determining what is needed in tackling a health challenge locally. With this focus on the interrelations among technological innovation, local needs, and comparisons across global distances, we aim to contribute to critical discussions of the prospects of traveling technologies for global health, as well as drawing attention to the recipient's agency in (re)shaping the capacity of the technology and thus the need-solution complex even in the face of powerful asymmetries.